Reversibility of the Martensitic Transformations and Shape-Memory Effects - Lobodyuk, V.A. (Успехи физики металлов, 2016)
The results of the investigations of main peculiarities and reversibility of the martensitic transformations in different materials are considered and discussed. So unusual mechanical properties as shape memory effect, superelasticity, superplasticity and others phenomena caused by these transitions are also analyzed. The values of the recovering deformation are defined by the mechanism of the martensitic transformations and its reversibility. Reasons for their differences in the alloys with different character of the martensitic transition are also discussed. Рассматриваются и обсуждаются результаты исследований основных особенностей и обратимости мартенситных превращений в различных материалах. Проводится анализ таких необычных механических свойств, как эффект памяти формы, сверхупругость, сверхпластичность и других явлений, вызванных такими переходами. Величины возвращаемой деформации определяются механизмом мартенситных превращений и их обратимостью. Также обсуждаются причины их разных значений в сплавах с различным характером мартенситных переходов. Розглядаються й обговорюються результати досліджень основних особливостей та оберненості мартенситних перетворень в різних матеріялах. Проводиться аналіза таких незвичайних механічних властивостей, як ефект пам’яті форми, надпружність, надпластичність та інших явищ, спричинених такими переходами. Величини відновлюваної деформації визначаються механізмом мартенситних перетворень та їх оберненістю. Також обговорюються причини їх різних значень в стопах із різним характером мартенситних переходів.